Penerapan manajemen strategi sebagai upaya peningkatan daya saing bank syariah di era globalisasi - Sulistyawati, Dewi Indah (Maliki Interdisciplinary Journal, 2025)
Globalization and digital technology pose both challenges and opportunities for Islamic banking. To maintain competitiveness, Islamic banks need to implement effective, adaptive, and innovative strategic management. This article uses a literature review of six recent studies at Indonesian state Islamic universities over the past five years, focusing on strategic planning, technology implementation, product and service innovation, strategy evaluation, and adaptation to global dynamics. The results of the study show that the integration of Islamic principles with adaptive strategies and digital innovation increases efficiency, customer loyalty, and the competitive position of banks in the global market. Furthermore, the study's findings confirm that the success of Islamic banks in navigating the digital era depends not only on technological aspects, but also on strengthening Islamic-based governance, increasing Islamic financial literacy, and collaborating with the fintech sector.